THE EFFECT OF ROOM MATERIAL TO OVER-COME THE NOISE DUE TO MOTORCYCLE WORKSHOP ACTIVITY AT HOME BASED-ENTERPRISED NEARBY ROADWAY - Petty Debriana Austin; Ima Defiana; Dhany Arifianto (Journal of Architecture&ENVIRONMENT, 2015)
Home based-enterprised is currently booming in Indonesia. Home based-enterprised is a right choice for people who want to have a business that integrates with their home. From some of business which has the highest noise level is a home with motorcycle repair business. Because the source of noise in the workshop is the engine and other supporting machinery. Home business is generally situated near from roadway and has acoustic problems aspect. Motorcycle repair service located near from roadway receives noise from inside and from outside (roadway).The sound sources distribute noise through building elements, such as walls, floors and ceilings. Thus it needs to be researched the elements of room that potentially reducing noise, especially noise that transmits through the airborne.To determine the noise level and effect that transmit through the airborne, the study using physical data collection with field studies. While the method using the experi-mental methods with simulation methods where in its implementation procedures use some software like Ms. Excel and Ecotect to analyze the Sound Pressure Level (SPL) and Transmission Loss.The result showed that the characteristic of the materials (Transmission Loss & Leq) influence on noise through the airborne. Thus it is obtained the right solution to overcome and reduce the noise at shophouse through the selection of appropriate material that can reduce airborne noise. The appropriate organic and anorganic material selection are expected to be the solution of the existing problems. The ex-periment results show that all of the material (organic & anorganic) can reach the goal, but the best result is combination of both material, the organic material and anorganic material.